The Role of Investigative Journalism in Indonesia’s Criminal Justice Reforms: A Legal Analysis - Bakhtiar, Handar Subhandi (Indonesia Media Law Review, 2025)
Investigative journalism plays a crucial role in upholding democratic values by exposing legal violations, corruption, and systemic injustices within Indonesia’s criminal justice system. However, various challenges, including political interference, restrictive legislation, and threats to press freedom, hinder its effectiveness. This study aims to analyse the impact of investigative journalism on legal reforms in Indonesia, focusing on its role in uncovering miscarriages of justice, judicial corruption, and human rights violations. Employing a qualitative research approach, this study utilises a case study method to examine high-profile cases. Data collection involves reviewing secondary sources, including investigative reports, legal documents, and media coverage. This study indicate that investigative journalism has significantly contributed to legal reforms by exposing judicial corruption, wrongful convictions, and abuses of power. Key cases such as Sengkon and Karta, Baiq Nuril, Artalyta Suryani, Munir, and Ferdy Sambo illustrate how media exposure generates public pressure, prompting institutional accountability and policy changes. Despite ongoing challenges including legal intimidation, defamation laws, and press freedom constraints investigative journalism remains a critical instrument for democratic oversight and legal transformation. Compared to other jurisdictions, Indonesia’s legal framework remains inadequate in safeguarding journalistic freedom and press independence.